ISLAMIC LAW STUDY AND MARRIAGE LAW ON MARRIAGE DISPENSATION - Sutriyono, Sutriyono; Mujahid Lidinillah, Ahmad (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Marriage dispensation as a legal solution because most of the perpetrators of marriage dispensation are those who do not yet have formal legality to marry, so they then take legal efforts so that the marriage they carry out can be recognized. This study aims to determine the perspective of Islamic law, the Marriage Law and the Compilation of Islamic Law on marriage dispensation. The method used is qualitative with primary data sources from the Marriage Law, the Fiqh Book and the Compilation of Islamic Law while secondary data are books, journals, magazines related to marriage dispensation. The results of this study found that Islamic Law does not specifically regulate marriage dispensation because the majority of scholars only mention balig as a requirement for someone to marry and do not determine the minimum age of marriage, while Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law strictly regulates underage marriage, namely it must go through a court hearing mechanism to obtain permission for marriage dispensation.